Análisis al proceso de suburbanización y políticas de control urbano. Caso de la ciudad de Riobamba, Ecuador - Tapia Moyano, Lisseth Mireya (2022)
The rapid suburban growth of the city of Riobamba has been evident since 1984. There are data on the first settlements outside the urban perimeter for reasons such as external migration from rural sectors. Other provinces seeking an improvement in their economy, business implantation external, internal migration, etc. these settlements were identified in 1990 in the first PDUR (1994) as San Gabriel, San Antonio (via Guano), San Antonio (via Penipe), San Martin, de Veranillo, Libertad, Pedregal, San José de Chibunga, Dolorosa and Lolita, their continuous expansion forced the Local Government to change its use from rural to urban land. Currently, there are data from new settlements such as Awisacte, El Batán, El Shuyo, El Troje, Libertad, La Lolita, Lican, San Antonio-Laguna, San Martin de Veranillo, Santa Ana-Buenos Aires, which due to their territorial occupation, have been called of social interest, which allows them to be part of the urban area. Suburbanization has been part of the expansion of the city, and the lack of policies to control it has consequences such as the rapid expansion of the territory with a low population density, accelerated and uncontrolled growth, etc. The present research aims to study the suburbanization process of the city of Riobamba in the periods 1984-1990, 1990-2000, 2000-2010, and 2010-2020 analyze Local Government policies, with the results obtained from the diagnosis are raised urban policies that make it possible to control excessive growth and increase the current population density.